The impact of the COVID-19 pandemic on sleep disorders among Nursing professionals - Carla Renata Silva Andrechuk; Juliano de Souza Caliari; Mariana Alvina dos Santos; Flávia Helena Pereira; Henrique Ceretta Oliveira; Maria Filomena Ceolim (Universidade de São Paulo, 2023)
Abstract Objective: to analyze the factors related to sleep disorders reported by Nursing professionals during the COVID-19 pandemic. Method: this is a cross-sectional and analytical study conducted with Nursing professionals from all Brazilian regions. Sociodemographic data, working conditions and questions about sleep disorders were collected. The Poisson regression model with repeated measures was used to estimate the Relative Risk. Results: 572 answers were analyzed, which revealed that non-ideal sleep duration, poor sleep quality and dreams about the work environment were predominant during the pandemic, with 75.2%, 67.1% and 66.8% respectively; as well as complaints of difficulty sleeping, daytime sleepiness and non-restorative sleep during the pandemic were reported by 523 (91.4%), 440 (76.9%) and 419 (73.2%) of the Nursing professionals, respectively. The relative risk of having such sleep disorders during the pandemic was significant for all variables and categories studied. Conclusion: non-ideal sleep duration, poor sleep quality, dreams about the work environment, complaints regarding difficulty sleeping, daytime sleepiness and non-restorative sleep were the predominant sleep disorders among Nursing professionals during the pandemic. Such findings point to possible consequences on health, as well as on the quality of the work performed.